2019
DOI: 10.1017/s0950268819000190
|View full text |Cite
|
Sign up to set email alerts
|

Feral cats do not play a major role in leptospirosis epidemiology on Reunion Island

Abstract: Although previous studies have reported Leptospira carriage in kidneys and urine of cats, the role of these animals in leptospirosis epidemiology remains poorly understood. Using molecular methods, we investigated Leptospira renal carriage in 172 feral cats from Reunion Island, an oceanic geographically isolated island located in the South West Indian Ocean. Only one out of the 172 analysed specimens tested positive for Leptospira DNA through quantitative real-time polymerase chain reaction. Using this positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…The prevalence of urinary shedding from leptospiral DNA in the present research is consistent with that reported in previous studies in cats [6,7,14,15,18,19]. Our results also match with those obtained by Sprißler et al, 2018 (0.8%) [14] and Gomard et al, 2019 (0.6%) [8]. In common, the two PCRs methodologies used in these two studies and in our work are targeting the lipL32 gene [25,48].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The prevalence of urinary shedding from leptospiral DNA in the present research is consistent with that reported in previous studies in cats [6,7,14,15,18,19]. Our results also match with those obtained by Sprißler et al, 2018 (0.8%) [14] and Gomard et al, 2019 (0.6%) [8]. In common, the two PCRs methodologies used in these two studies and in our work are targeting the lipL32 gene [25,48].…”
Section: Discussionsupporting
confidence: 93%
“…Catalonia and Extremadura are two of the autonomous communities with the highest reported cases [4,5]. It has been shown that some pathogenic species of leptospires like Leptospira borgpetersenii, Leptospira interrogans, and Leptospira kirschneri can naturally infect cats [6][7][8]. Clinical presentation of the disease is rare and usually mild in cats [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serological evidence of cat infection have been published in countries such as Chile, 58 and cats can shed leptospires in their urine during acute clinical infection and may even act as chronic shedders. 59 61 Furthermore, their involvement in the epidemiological cycle in rural areas is suspected. 62 Dogs, mainly stray dogs, have been also suspected or are involved in the epidemiology of human leptospirosis worldwide, including in the SWIOIs.…”
Section: Discussionmentioning
confidence: 99%
“…31,18 Some cats with antibodies against Leptospira species have been found to have signs associated with renal disease and/or histopathological evidence of renal inflammation. 14,16,30,35,59 As in dogs, leptospirosis in cats can cause acute kidney injury that leads to chronic kidney disease. 19,60 Lesions in the liver of affected cats have been reported less commonly than in dogs.…”
Section: Diagnosismentioning
confidence: 99%